OPTIMIZING PRODUCTIVITY IN SEPARATING BIOMASS AND ORGANIC MATERIALS FROM PALM OIL MILL EFFLUENT: EXPERIMENT TOWARDS REDUCING CARBON EMISSION FOR CLIMATE CHANGE AFFECT - Shahidul, M.I.; Malcolm, M.L.; Eugene, J.J.; Sharafatul, M.I. (2020)
This paper describes a problem that exists in palm mill effluent treatment; and also presents a technologically and environmentally sustainable solution achieved from experimental research. At the first stage, a two-stage continuous anaerobic reactor with carbon to Nitrogen ratio enrichedinoculum has used for the digestionbiomass and organic materials of POME. In the second stage, Nanomembranes have used for separating biomass and organic materials from effluent discharge from TBAR. This research investigatedthe performanceof the anaerobic reactor and the Nano membrane in reducing organic materials and biomass from POMEfor producing dischargeable effluent.Theanaerobic reactor was operated at temperature 350C with various range of manipulating variables; the outcome of research haddemonstrated a 62.5 % digesting performance of biomass and organic materials. The Nano membrane system was operated at a feed pressure range of 60 psi to 120 psi, which haddemonstrated over 95% performance in separating biomass and organic materials from the effluent discharged fromthe anaerobic reactor. The findings of this research would be useful in POME treatment for optimizing the environmentally friendly effluent production for recycling as process water for the crude palm oil process. However, the novelty of this research is to use a two-stage anaerobic reactor and Nanomembranes system in series inoptimizing the performance and operating cost in POME treatment.